An implementation science approach for developing and implementing a dietitian-led model of care for gestational diabetes: a pre-post study - Nina MELONCELLI; Adrian BARNETT; Susan de JERSEY (BMC, 2020)
Abstract Background There is strong evidence that women with gestational diabetes mellitus (GDM) who receive a minimum of three appointments with a dietitian may require medication less often. The aim of this study was to evaluate the impact of a dietitian-led model of care on clinical outcomes and to understand the utility of the integrated Promoting Action on Research Implementation in Health Services (i-PARIHS) framework as a prospective tool for implementation. Methods This was a pre-post intervention study measuring outcomes before-and-after changing a gestational diabetes (GDM) model of care and included women with GDM managed at a large, regional hospital in Queensland, Australia. The i-PARIHS framework was used to develop, implement and evaluate a dietitian-led model of care which increased dietetic input for women with GDM to a minimum of one initial education and two review appointments. The outcomes were adherence to the schedule of appointments, clinician perspective of the implementation process, pharmacotherapy use, gestational age at commencement of pharmacotherapy and birth weight. Pre- and post- comparisons of outcomes were made using t-tests and chi-squared tests. Results Adherence to the dietetic schedule of appointments was significantly increased from 29 to 82% (p < 0.001) but pharmacotherapy use also increased by 10% (p = 0.10). There were significantly more women in the post-intervention group who were diagnosed with GDM prior to 24 weeks gestation, a strong independent predictor of pharmacotherapy use. Infant birthweight remained unchanged. The i-PARIHS framework was used as a diagnostic tool and checklist in the model of care development phase; a facilitation tool during the implementation phase; and during the evaluation phase was used as a reflection tool to identify how the i-PARIHS constructs and their interactions that may have impacted on clinical outcomes. Conclusions The i-PARIHS framework was found to be useful in the development, implementation and evaluation of a dietitian-led model of care which saw almost 90% of women with GDM meet the minimum schedule of dietetic appointments.